Intermittent theta burst stimulation attenuates oxidative stress and reactive astrogliosis in the streptozotocin-induced model of Alzheimer’s disease-like pathology - Stanojevic, Jelena B.; Zeljkovic, Milica; Dragic, Milorad; Stojanovic, Ivana R.; Ilic, Tihomir V.; Stevanovic, Ivana D.; Ninkovic, Milica B. (Frontiers in Aging Neuroscience, 2023)
Introduction Intracerebroventricularly (icv) injected streptozotocin (STZ) is a widely used model for sporadic Alzheimer’s disease (sAD)-like pathology, marked by oxidative stress-mediated pathological progression. Intermittent theta burst stimulation (iTBS) is a noninvasive technique for brain activity stimulation with the ability to induce long-term potentiation-like plasticity and represents a promising treatment for several neurological diseases, including AD. The present study aims to investigate the effect of the iTBS protocol on the animal model of STZ-induced sAD-like pathology in the context of antioxidant, anti-inflammatory, and anti-amyloidogenic effects in the cortex, striatum, hippocampus, and cerebellum. Methods Male Wistar rats were divided into four experimental groups: control (icv normal saline solution), STZ (icv STZ—3 mg/kg), STZ + iTBS (STZ rats subjected to iTBS protocol), and STZ + Placebo (STZ animals subjected to placebo iTBS noise artifact). Biochemical assays and immunofluorescence microscopy were used to evaluate functional and structural changes. Results The icv STZ administration induces oxidative stress and attenuates antioxidative capacity in all examined brain regions. iTBS treatment significantly reduced oxidative and nitrosative stress parameters. Also, iTBS decreased Aβ-1-42 and APP levels. The iTBS enhances antioxidative capacity reported as elevated activity of its enzymatic and non-enzymatic components. In addition, iTBS elevated BDNF expression and attenuated STZ-induced astrogliosis confirmed by decreased GFAP+/VIM+/C3+ cell reactivity in the hippocampus. Discussion Our results provide experimental evidence for the beneficial effects of the applied iTBS protocol in attenuating oxidative stress, increasing antioxidant capacity and decreasing reactive astrogliosis in STZ-administrated rats.